A Comparative Review on Polyhydroxybutyrate (PHB) Production by Bacillus megaterium Using Different Substrates under Batch Fermentation - Chintya Sinar Lumbantoruan; F.B.A. Fitriani (Department of Chemical Engineering, Faculty of Engineering, Universitas Diponegoro, 2025)
The use of non-degradable plastics as packaging has led to significant environmental issues because they are resistant to degradation and contributes to environmental pollution. The application of biodegradable plastics offers a potential solution to this problem. Polyhydroxybutyrate (PHB) is an environmentally friendly thermoplastic polyester polymer that exhibits advantageous properties compared to conventional plastics, especially its biodegradability. The synthesis of PHB can be achieved through three main routes: synthetic polymerization, genetic engineering, and microbial fermentation. This paper aims to explore most suitable substrate used for PHB biosynthesis via batch microbial fermentation based on the highest yield. The microorganism employed in PHB biosynthesis was Bacillus megaterium, which utilized substrates, such as cheese whey, sugarcane molasses, glucose, and glycerol. The highest PHB yield, 8.29 g/L, was obtained when cheese whey was used as the substrate. These finding indicates that cheese whey provides an excellent nutrient source for PHB production.